Entering the Magic Mists: Irish Contemporary Paganism, Celticity and Indigeneity. (16th November 2018) - Butler, Jenny
Abstract : This article explores the ways in which contemporary Pagans in Ireland engage with traditional culture, as well as with notions of the Celtic, in forming identities that are regarded by some practitioners as being indigenous identities. This cultural process at work in the Pagan movement is examined against a backdrop of contested constructions of "Irishness" in different political and sociocultural milieus. Drawing from ethnographic research on the Irish Pagan community, the examination includes examples of mechanisms used by modern Pagans to engage with ancestral and historical cultures. In entering the magic mists to search for symbols and ideas to help connect to the "old religion, " modern Pagans create something new and unique while taking inspiration from the past. This overview of Pagans' utilization of cultural forms, and their use of tradition, aims to communicate why this creative approach to the past, and resulting formation and maintenance of identities, is culturally significant in the Irish context.